Upaya Peningkatan Output Produksi di PT. X - Setiawan, Aldo Christianto; Octavia, Tanti (Jurnal Titra, 2015)
PT X is a clothing company that produces bags and floor math. The problem that occured is unfulfilled the companyâs target. The average of production output is only 24.82% of the capacity. Some of the causes of the problem are the production output decreased after 14.30 pm, the workers did not reach the target, and the decreasing of production output day after delivery the finished goods as 37.3%.The proposed improvements are company should provide target for each process of production and avoid the delivery of finished goods on Friday.